Dose-ranging and safety with intravenous levosimendan in low-output heart failure Experience in three pilot studies and outline of the levosimendan infusion versus dobutamine (LIDO) trial - Follath F.; Hinkka S.; Jager D.; Just H.; Mitrovic V.; Papp Gyula; Peuhkurinen K.; Sandell E. P.; Takkunen O.; Lehtonen L. (1999)
A series of dose-ranging and tolerability studies of intravenous levosimendan (bolus then infusion) were conducted in 40 patients with low-output heart failure (cardiac index <2.5 L/m(2) per minute). These trials were conducted as preparation for the Levosimendan Infusion versus Dobutamine (LIDO) study, an international, randomized, comparative phase III trial of intravenous levosimendan versus dobutamine in heart failure. Response rates to levosimendan therapy (defined as greater than or equal to 30% Increase In cardiac index during levosimendan administration) were 73-100% (compared with 60% with dobutamine 8-16 mu g/kg per minute). Dose dependence was apparent in several hemodynamic responses to levosimendan. From experience in these studies it was concluded that the preferred bolus dose for initiating levosimendan therapy was 12-24 mu g/kg, followed by infusion at rates vp to 0.4 mu g/kg per minute. It was also concluded that, in the dose range identified, levosimendan offered a valid alternative to dobutamine in heart failure patients who require intravenous inotropic support.
Keywords: Általános orvostudomány; Klinikai orvostan